Hsp90 inhibition ameliorates CD4+ T cell‐mediated acute Graft versus Host disease in mice. Issue 4 (10th October 2016) - Berges, Carsten; Kerkau, Thomas; Werner, Sandra; Wolf, Nelli; Winter, Nadine; Hünig, Thomas; Einsele, Hermann; Topp, Max S.; Beyersdorf, Niklas
Abstract: Introduction: For many patients with leukemia only allogeneic bone marrow transplantion provides a chance of cure. Co‐transplanted mature donor T cells mediate the desired Graft versus Tumor (GvT) effect required to destroy residual leukemic cells. The donor T cells very often, however, also attack healthy tissue of the patient inducing acute Graft versus Host Disease (aGvHD)—a potentially life‐threatening complication. Methods: Therefore, we used the well established C57BL/6 into BALB/c mouse aGvHD model to evaluate whether pharmacological inhibition of heat shock protein 90 (Hsp90) would protect the mice from aGvHD. Results: Treatment of the BALB/c recipient mice from day 0 to +2 after allogeneic CD4 + T cell transplantation with the Hsp90 inhibitor 17‐(dimethylaminoethylamino)‐17‐demethoxygeldanamycin (DMAG) partially protected the mice from aGvHD. DMAG treatment was, however, insufficient to prolong overall survival of leukemia‐bearing mice after transplantation of allogeneic CD4 + and CD8 + T cells. Ex vivo analyses and in vitro experiments revealed that DMAG primarily inhibits conventional CD4 + T cells with a relative resistance of CD4 + regulatory and CD8 + T cells toward Hsp90 inhibition. Conclusions: Our data, thus, suggest that Hsp90 inhibition might constitute a novel approach to reduce aGvHD in patients without abrogating the desired GvT effect. Abstract : Here we show that Hsp90 inhibition using 17‐(dimethylaminoethylamino) 17‐demethoxygeldanamycin (DMAG) or NVP‐AUY922 partially protected mice from aGvHD whereas the beneficial Graft versus Tumor (GvT) activity was preserved. Furthermore, in vivo analyses and in vitro experiments revealed that CD4 + Foxp3 + regulatory T cells were far less affected by Hsp90 inhibition than CD4 + Foxp3‐ conventional T cells and CD8 + T cells. Our data, thus, suggest that Hsp90 inhibition might constitute a novel approach to reduce aGvHD in patients without abrogating the desired GvT effect.